Fe(III)-Based Nanomicelles for Magnetic Resonance Imaging of Colorectal Cancer with Hepatic Metastasis - Tianlun Shen; Kaiwei Lv; Zhenyan Chen; Songyi Xu; Guangyao Li; Guocan Han; Yì Xiáng J. Wáng; Jun Ling; Jihong Sun (Journal of Functional Biomaterials)
Colorectal cancer (CRC) is a leading global malignancy with a poor prognosis in advanced stages. Early and accurate diagnosis remains challenging due to the overlapping of clinical manifestations between early-stage CRC and inflammatory bowel diseases. Although dynamic contrast-enhanced MRI (DCE-MRI) is a critical imaging modality for the diagnosis of CRC and colorectal cancer liver metastasis (CRLM), conventional gadolinium-based contrast agents (GBCAs) have the limitations of rapid clearance and potential toxicity risks. In this study, we report a gadolinium-free T1-weighted nanocontrast agent based on Fe(III)-coordinated poly(α-amino acid)s (Fe@POS) nanomicelles. Fe@POS nanomicelles exhibit a high longitudinal relaxivity (r1 = 5.56 mM−1s−1) and prolonged blood circulation time with selective CRC tumor accumulation via enhanced permeability and retention (EPR) effect. In vivo MRI studies revealed long-period MRI of CRC. In CRLM lesions, normal hepatic tissue demonstrates greater Fe@POS uptake compared to tumor tissue, which enables clear delineation of tumor margins on MRI. Histological and biochemical analysis confirmed the biocompatibility of Fe@POS nanomicelles, with no acute toxicity observed, highlighting their potential as alternatives to GBCAs for clinical diagnostic applications.